Deformation and migration characteristics of bubbles moving in gas-liquid countercurrent flow in annulus - Bangtang YIN; Tianbao DING; Shulong WANG; Zhiyuan WANG; Baojiang SUN; Wei ZHANG; Xuliang ZHANG (Petroleum Exploration and Development)
The gas-liquid countercurrent flow pattern is complex and the bubble migration velocity is difficult to predict in the process of bullheading well killing. The experiment on bubble migration in gas-liquid countercurrent flow in annulus is carried out under different working conditions to reveal how the wellbore inclination angle, liquid phase property and countercurrent liquid velocity affect the bubble deformation and bubble migration trajectory/velocity, and to establish a bubble migration velocity prediction model. The bubbles in the countercurrent flow mainly migrate in two modes: free rising of isolated bubbles, and interactive rising of multiple bubbles. The bubbles migrate by an S-shaped trajectory in the countercurrent flow. With the increase of countercurrent liquid velocity, the lateral oscillation of bubbles is intensified. The increases of wellbore inclination angle, liquid density and liquid viscosity make the bubble migration trajectory gradually to be linear. The bubble is generally ellipsoidal during its rising. The wellbore inclination angle has little effect on the degree of bubble deformation. The bubbles are ellipsoidal during rising, with little influence of wellbore inclination angle on bubble deformation. With the increase of liquid viscosity and density, the aspect ratio of the bubble decreases. As the wellbore inclination angle increases, the bubble migration velocity gradually decreases. As the liquid viscosity increases, the bubble migration velocity decreases. As the liquid density increases, the bubble migration velocity increases slightly. The established bubble migration velocity prediction model yields errors within ± 15 %, and demonstrates broad applicability across a wide range of operating conditions.